Genetic variants in microRNA genes: impact on microRNA expression, function, and disease - Cammaerts, Sophia; Strazisar, Mojca; De Rijk, Peter; Del Favero, Jurgen (Frontiers in Genetics, 2015)
MicroRNAs are important regulators of gene expression and like any other gene, their coding sequences are subject to genetic variation. Variants in microRNA genes can have profound effects on miRNA functionality at all levels, including microRNA transcription, maturation and target specificity, and as such they can also contribute to disease. The impact of variants in microRNA genes is the focus of the present review. To put these effects into context, we first discuss the requirements of microRNA transcripts for maturation. In the last part an overview of available databases and tools and experimental approaches to investigate miRNA variants related to human disease is presented.